IMPACT OF SOCIODEMOGRAPHIC AND CLINICAL VARIABLES ON THE QUALITY OF LIFE OF PATIENTS WITH SKIN LESIONS - Guimarães Teixeira Souto, Simone; Cristina Santos Alves Souto, Elaine; Alencar Fróes Esteves, Kênia; Afonso Fagundes Pereira, Fabíola; Fagundes Souto, Daniella; Guimarães Teixeira, Marcelo; de Freitas Gomes Ruas, Edna; Gomes e Martins, Aurelina; Carlos Pereira de Jesus, Ely; Fonseca Almeida, Fernandez; Emanuel Santos Pimenta, Hugo; Fernandes do Prado, Patrícia; et al. (Revista Gênero e Interdisciplinaridade, 2026)
Objective: To evaluate the quality of life of patients with chronic skin lesions and associated factors. Methods: a descriptive-exploratory, cross-sectional study with a quantitative approach was carried out in Montes Claros, Minas Gerais – Brazil at the Wound Outpatient Clinic with 18 patients diagnosed with chronic skin lesions. The dependent variable quality of life was assessed using the Wound-Qol questionnaire, which assesses the disease-specific health-related quality of life of patients with chronic skin lesions. Descriptive analysis, quality of life score analysis, bivariate analysis, and crude and adjusted prevalence ratios were estimated with their respective 95% confidence intervals and 5% significance level. The Poisson model with robust variance was adopted. Variables with a p-value ≤ 0.20 were selected for multiple analysis. Results: the daily life and psychological domains obtained the highest levels of impairment, impairing the overall score of general quality of life, and the highest scores were concentrated in the “body and financial” domain. Self-reported lack of physical activity, alcoholism, and injury exudate were associated with quality of life. Conclusion: the quality of life of patients with chronic skin lesions is multifactorial and complex, requiring comprehensive and interdisciplinary action by health professionals beyond the reductionist view of the lesion